The different facets of organelle interplay—an overview of organelle interactions - Islinger, Markus; Godinho, Luis F.; Costello, Joseph; Schrader, Michael (Frontiers in Cell and Developmental Biology, 2015)
Membrane-bound organelles such as mitochondria, peroxisomes or the endoplasmic reticulum (ER) create distinct environments to promote specific cellular tasks such as ATP production, lipid breakdown or protein export. During recent years, it has become evident that organelles are integrated into cellular networks regulating metabolism, intracellular signalling, cellular maintenance, cell fate decision and pathogen defence. In order to facilitate such signalling events, specialized membrane regions between apposing organelles bear distinct sets of proteins to enable tethering and exchange of metabolites and signalling molecules. Such membrane associations between the mitochondria and a specialized site of the ER, the mitochondria associated-membrane (MAM), as well as between the ER and the plasma membrane (PAM) have been partially characterized at the molecular level. However, historical and recent observations imply that other organelles like peroxisomes, lysosomes and lipid droplets might also be involved in the formation of such apposing membrane contact sites. Alternatively, reports on so-called mitochondria derived-vesicles (MDV) suggest alternative mechanisms of organelle interaction. Moreover, maintenance of cellular homeostasis requires the precise removal of aged organelles by autophagy – a process which involves the detection of ubiquitinated organelle proteins by the autophagosome membrane, representing another site of membrane associated-signalling. This review will summarize the available data on the existence and composition of organelle contact sites and the molecular specializations each site uses in order to provide a timely overview on the potential functions of organelle interaction.